Pengaruh Musik dalam Mengembangkan Kemampuan Mengenal Bilangan Siswa Kelompok A di TK Lintang Surabaya - Isabella Hasiana; Aniek Wirastania (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
Understanding the concept of numbers is something that is especially important for young children. This is because the numbers we always use throughout the life process. Also understanding numbers is the first step of a mathematics lesson, without an understanding of numbers, then a child will have difficulty in the next stage of learning. This study aims to develop the ability to recognize the number of students of group A through guidance program using music media. Using quasi-experimental design used in this research is non-equivalent pretest-posttest control group design which is done in field test of guidance program using music media in increasing the ability to recognize the number in child of Kindergarten Group A at Lintang Kindergarten. The result of this research is analyzed by T test formula which is done using help SPSS program. Based on the results of research conducted obtained with sig (0,000) 0.05 which means there is a difference between the experimental group with the control group in recognizing the number symbols by using music. So it can be concluded that the guidance program by using music media that has been compiled can be said to have an effect in improving the ability to recognize the numbers in children group A.